Photovoltaic panels have altered grassland plant biodiversity and soil microbial diversity - Bai, Zhenyin; Jia, Aomei; Bai, Zhenjian; Qu, Shanmin; Zhang, Meng; Kong, Linghang; Sun, Renhao; Wang, Mingjun (Frontiers in Microbiology, 2022)
Abstract: Human concerns about fossil fuel depletion, energy security and environmental degradation have driven the rapid development of solar photovoltaic power (PV) generation. Most of the photovoltaic power generation plants are concentrated in desert, grassland and arable land, which means the change of land use type. However, there is still a gap in the research of the PV panel layout on grassland diversity and ecological function. In this study, Illumina high-throughput sequencing technology was used to investigate the effects of PV panel arrangement on grassland plant and soil microbial diversity. In view of the differences in the microclimate at different locations of the PV panels, quadrates were arranged in front edge (FE), beneath the center of each panel (BP), back edge (BE), the uncovered interspace adjacent to each panel (IS) and the undisturbed grassland around the PV panels (Control), respectively. PV panels (especially FE) significantly increased the total aboveground productivity (Total AGB) and plant species diversity in grasslands. The change of microclimate and plant diversity directly and indirectly changed the diversity of soil bacterial and fungal communities. PV panels decreased the relative abundance of Actinobacteriota, while increased the relative abundance of Proteobacteria, Acidobacteriota, and Methylomirabilota. EC, Margalef’ s richness and Total AGB were the main factors affecting the composition of bacterial communities, while AN and AP were the main factors affecting the composition of fungal communities. In conclusion, the arrangement of PV panels increased the diversity of plant communities and soil microorganisms in grassland. This study provides important information for further understanding the impact of PV panels on grassland ecosystem function, and is of great significance for maintaining grassland ecosystem function.